Enhancing the wound healing potential using earthworm clitellum factors and elucidating its molecular mechanism in an in-vitro and earthworm model - Kamarajan Rajagopalan; Jackson Durairaj Selvan Christyraj; Johnson Retnaraj Samuel Selvan Christyraj; Meikandan Chandrasekar; Nivedha Balamurugan; Nandha Kumar Suresh; Puja Das; Ashwin Barath Vaidhyalingham; Leela Bharathiraja (Scientific Reports)
Abstract Earthworm, Eudrilus eugeniae cannot survive and regenerate without clitellum segments. In regenerating worms, the clitellum’s epithelial and circular muscular layers are reduced to one-third, and longitudinal cell layers to half. In C2C12 cells, Clitellum Factors (CF − 5, 25 and 50%) and Regenerative Clitellum Factors (RCF − 5, 25, 50, 75%) ameliorate the cell viability up to 20–28% and 30–38% respectively than the control. In contrast, extracts from body segments negatively influence cell viability up to 80%. In a scratch-wound assay, 25% RCF and 5% CF achieved 99.86% and 81.54% wound closure in 24 h, respectively, compared to 40% in controls. RCF and CF also possess enhanced anti-microbial activity against gram + ve bacteria. Western Blotting reveals that Wnt3a, HoxD3 and VEGF were remarkably upregulated in RCF and CF treated samples and their upregulated stemness property is effectively regulated by p53, TCTP, H2AX, Cleaved Caspase-3 proteins. Immunofluorescence data clearly states that Wnt3a and Caspase-3 signals are more profoundly observed in nuclear over cytoplasm in RCF treated samples and H2AX shows less nuclear signals than CF. In in-vivo earthworm model conditions, RCF remarkably promotes the survivability and wound healing ability by promoting the Wnt3a and VEGF expression together with downregulation of Cox2.